ANALISIS TINGKAT KEPUASAN KONSUMEN DAN KINERJA WARKOP KEMANG MANADO (Analysis the Level of Consumer Satisfaction and Performance of Warkop Kemang Manado) - Christian David Parengkuan; Theodora M. Katiandagho; Ellen G. Tangkere (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2020)
This study aimed to analyse the level of consumer satisfaction at Warkop Kemang Manado and to formulate performance improvements of Warkop Kemang Manado. This research was conducted from November 2019 until April 2020. The data used in this study were primary and secondary data. Primary data were obtained from direct interviews with 44 respondents using a questionnaire, while secondary data were obtained from the business management. The results showed that, the value of the Customer Satisfaction Index (CSI) was 83.53 percent. It generally fallen in the